THE ROLE OF PLAY IN THE SCHOOL INCLUSION OF CHILDREN WITH DISABILITIES - Alves dos Santos, Sirlei (Revista Gênero e Interdisciplinaridade, 2025)
This article explores the role of play in the school inclusion of children with disabilities, highlighting how play activities can facilitate the integration and development of these children in the educational environment. Through a literature review and case studies, the study analyzes how play contributes to the socialization, learning and emotional well-being of children with disabilities. The article identifies playful practices and strategies that promote inclusion, such as adapted games, cooperative activities and the use of assistive technologies. Furthermore, it discusses the importance of an inclusive approach on the part of educators, who must be prepared to create a welcoming and accessible environment. It is concluded that play is a powerful tool for school inclusion, capable of breaking down barriers and fostering an environment of respect and appreciation of diversity. It is recommended that schools systematically integrate play into their pedagogical practices to promote inclusive and equitable education.